Sinful Money: Attitudes to Coins in Second Temple Judaism and the Origins of Christianity - Visi, Tamás (Journal for the study of the historical Jesus, 2026)
In Jewish religious literature of the Second Temple period, coins as physical objects were closely associated with the sins that were committed through them. Such ‘tainted money’ could bring about bad luck or divine punishment to its owner according to the mindset of the authors. Some of the religious ideals reflected in early Christian texts can be interpreted as responses to the anxiety about sinful money too. Ascetic life in desert and voluntary poverty were both capable of neutralizing the sinful nature of coins. In particular, the image of John the Baptist in New Testament texts suggests that at the core of the Baptist’s success was anxiety about sinful money.